Household preferences and governance of water services: A hedonic analysis from rural Guatemala - Vásquez, William F. (International Food Policy Research Institute, 2011)
This paper estimates hedonic models of rental prices to investigate household preferences regarding water services in rural Guatemala. Estimated values for water services are compared across municipal, private, and community-managed water utilities. Findings indicate that rural households value municipal water services but are indifferent between not having piped water and being connected to a private system. Moreover, the estimated value of community-managed services is negative, which suggests that rural households have an aversion to services managed at the community level. It is argued that the value households assign to water services reflects institutional costs imposed by the forms of service governance here analyzed.